Peran Psikologi dalam Pendidikan Islam - Suyatman, Suyatman; Rokhimah, Siti (Lembaga Yasin AlSys, 2026)
Islamic education is a comprehensive process of human development encompassing physical, intellectual, and spiritual dimensions grounded in Islamic values, and therefore cannot be separated from psychological inquiry, which offers an in-depth understanding of learners’ development, behavior, needs, and character. This paper aims to examine the role of psychology in Islamic education and its contribution to enhancing the effectiveness of the learning process and the formation of students’ personalities. A library research method was employed by analyzing various relevant literature sources from the perspectives of psychology and Islamic education. The findings show that psychology plays a crucial role in helping educators understand learners’ developmental stages, individual differences, learning motivation, and the emotional and social aspects that influence the educational process. The integration of psychological principles with Islamic values enables the implementation of an educational process that is more humanistic, effective, and aligned with human fitrah. Thus, psychology holds a strategic role in supporting the goals of Islamic education, namely to shape individuals who are faithful, of noble character, knowledgeable, and capable of fulfilling their roles as servants of Allah and as khalifah on earth.